2023
DOI: 10.1128/spectrum.01173-23
|View full text |Cite
|
Sign up to set email alerts
|

Diverse genotypes of human enteric and non-enteric adenoviruses circulating in children hospitalized with acute gastroenteritis in Thailand, from 2018 to 2021

Arpaporn Yodmeeklin,
Kattareeya Kumthip,
Nuthapong Ukarapol
et al.

Abstract: Human adenovirus (HAdV) is a common viral pathogen that causes diarrhea in children worldwide. The aim of this study was to investigate the prevalence and genotype diversity of HAdV strains circulating in children admitted to the hospitals with acute gastroenteritis (AGE) in Chiang Mai, Thailand, from 2018 to 2021. A total of 1,790 stool samples were screened for HAdV by PCR method, and 80 (4.5%) were positive for HAdV. Of these, children under 5 years of age accounted for 90.0% of HAdV-positive cases with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
2
1
Order By: Relevance
“…32 Mixed infection of HAdV with other enteric viruses in pediatric patients with AGE has been reported previously worldwide. 13,16,18,[33][34][35][36][37][38][39] In this study, mixed infection of HAdV with other enteric viruses was detected at a very high infection rate of 63.6%, which is much higher than those reported previously, and only 36.4%…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…32 Mixed infection of HAdV with other enteric viruses in pediatric patients with AGE has been reported previously worldwide. 13,16,18,[33][34][35][36][37][38][39] In this study, mixed infection of HAdV with other enteric viruses was detected at a very high infection rate of 63.6%, which is much higher than those reported previously, and only 36.4%…”
Section: Discussioncontrasting
confidence: 62%
“…5,6 Among HAdV species, epidemiological studies demonstrated that enteric species F (genotypes 40 and 41) are the major species that caused AGE in pediatric patients. [7][8][9][10] Furthermore, nonenteric species such as types C1, C2, B3, C6, A31, and others are also frequently found in the diarrheal stool specimens, [11][12][13] and it is unclear whether these non-enteric types are associated with the patient's symptoms or not.…”
mentioning
confidence: 99%
“…Norovirus was identified as the predominant co-infection agent, accounting for 50% (16 out of 32) of co-infection cases. It should be noted that norovirus was more frequently detected in patients with AGE in Thailand during the same period ( Jampanil et al, 2021 ; Wei et al, 2021 ; Phengma et al, 2022 ; Hogben et al, 2023 ; Yodmeeklin et al, 2023 ). Similarly, adenovirus was the most predominant virus detected in AGE patients in Spain from 2013 to 2017, and it was found to be the most common co-infection virus detected in EV-positive cases ( Perez-Martinez et al, 2021 ).…”
Section: Discussionmentioning
confidence: 92%